A influência da arquitetura de Caryocar brasiliense (Caryocaraceae) sobre a ocorrência de aranhas no Cerrado - Coleta, Graziella Dela (2004)
The configuration of the vegetation is correlated to the distribution of resources in each habitat. This way, the structural complexity of the habitat may affect the diversity of species. However, few studies have been done about the spatial or architectural properties of the habitat, although this is of great importance in the habitat selection by many invertebrates, including specially predatory animais. The objective of this study was to determine the relationship between the plant architecture of Caryocar brasiliense (Caryocaraceae - popular pequi) and the presence and diversity of tree spiders in brazilian savanna. The studied areas were the Reserva do Clube de Caça e Pesca Itororó de Uberlândia (CCPIU), the Parque Estadual da Serra de Caldas Novas (PESCAN) and Buriti Farm, all three inserted in the Cerrado domain. The field data were collected at dawn (5 to 7:30 a.m.) or dusk (5:30 to 8 p.m.) and the methods were manual searching and entomological tray. The spiders were conserved in 70% ethanol and the phenology of each plant was determined, through the following parameters: height of the plant, number of branches, leaves, sprouts, flowers and ffuits. The statistical analysis revealed that there is a positive correlation between the number of leaves, as well as the branches, and the number of spiders. All the others parameters did not result in significant values when correlated to the number of spiders. These results indicate that the niche segregation is more horizontal than vertical, meaning that the abundance of spiders depends less on the height of the plant and more on its architectural diversity. Since the number of flowers influences the presence of herbivores, the spiders’ preys, it is suggested that the food and hiding places availability are the main factors determining these results.